A comparative study on machining and tool performance in friction drilling of difficult-to-machine materials AISI304, Ti-6Al-4V, Inconel718. (January 2021) - Dehghan, Shayan; Soury, Ehsan; Ismail, Mohd Idris Shah b.
Abstract: As a non-conventional drilling process, friction drilling has been successfully used for sheet metal hole-making, increasing the effectiveness of thread length, and screw coupling. The main challenges and obstacles to the implementation of the friction drilling process for difficult-to-machine materials are excessive tool wear and inadequate product quality. This study aims to investigate the effect of the two most significant parameters namely spindle speed and feed rate on bushing formation quality and drilling tool performance, and determination of optimal process parameters experimentally and numerically, both. Firstly, by using the full factorial method the experiments are designed. Then, the collected experimental data are statistically evaluated by analysis of variance (ANOVA) using the MINITAB tool. The findings reveal that spindle speed is a more significant parameter than feed rate that intensively affects machining and drilling tool performance. Moreover, the resultant optimum parameters combination for AISI304 is spindle speed 1000 rpm and feed rate 105 mm/min, for Ti-6Al-4 V is spindle speed 1000 rpm and feed rate 145 mm/min, and for Inconel718 is spindle speed 1500 rpm and feed rate 145 mm/min. Above all else, because of the good creep-rupture resistance of Inconel718, this material presents a great reaction concerning the high quality of formed-bush and drilling tool performance. Contrariwise, the low thermal conductivity of Ti6Al-4 V causes insufficient heat transfer throughout the workpiece, poor product quality, and severe tool wear. On the other hand, the effects of feed rate and spindle speed on the distribution of thermal stress and heat generation on workpieces are studied numerically. This proves the great potential of finite element analysis for an optimization study.